Biologia do psilídeo Russelliana solanicola Tuthill, 1959 (Hemiptera: Psyllidae) em losna-branca (Parthenium hysterophorus L.) (Heliantheae: Asteraceae) - Adabbo, Carolina Costa (Universidade Federal de São Carlos, 2023)
Psyllids (Hemiptera: Psyllidae) are sap-sucking insects that exhibit high host specificity. The phytopathogenic bacterium “Candidatus Liberibacter solanacearum” (CaLsol) is associated with several vegetable crops, mainly potato and carrot, and is transmitted both through propagative material and by psyllid vectors. In Brazil, this bacterium is classified as a quarantine pest (A1 category), meaning it is absent from the country. However, the polyphagous psyllid Russelliana solanicola Tuthill, 1959, occurs in Brazil and represents a potential vector of this pathogen, as it develops on solanaceous plants. The aim of the present study was to determine the life cycle of R. solanicola on Parthenium hysterophorus (losna-branca) and to establish a laboratory rearing methodology. Two methods were developed for R. solanicola rearing: a clip-cage and a cage for rearing the insect on seedlings or plants of P. hysterophorus. For illustrating developmental stages and measuring the longitudinal body length of R. solanicola, 15 specimens from each stage were used. Images were captured using a stereomicroscope (16x). The rearing of R. solanicola began with the collection of nymphs and adults from areas where P. hysterophorus occurs. The seedlings were transplanted into 1.5 L pots and, after 15 days, infested with R. solanicola individuals. Twenty-five mating pairs were confined in clip-cages to assess developmental stages (from the embryonic period to adult emergence). The parameters evaluated were: development time, egg and nymph stage viability, sex ratio, and mortality rate. The results showed that R. solanicola reached adulthood in 24.92 ± 1.55 days. Females laid an average of 149.96 ± 28.63 eggs. The sex ratio was 0.56, indicating a slight female bias. Males lived on average 13.64 ± 0.51 days, while females lived 10.64 ± 0.25 days. The total mortality from immature stage to adulthood was 32.46%. These findings confirm that R. solanicola completes its life cycle on P. hysterophorus, demonstrating the suitability of this plant as a host and providing a basis for establishing monitoring and management strategies. The methodologies developed proved to be feasible, low-cost, and adaptable, contributing to bioecological studies and to the prevention of potential phytosanitary risks.
Biology of the psyllid Russelliana solanicola Tuthill, 1959 (Hemiptera: Psyllidae) on white ragweed (Parthenium hysterophorus L.) (Heliantheae: Asteraceae)
Keywords: CaLsol; Plantas hospedeiras; Potencial vetor; Host plants; Potential vector; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE; 2. Fome Zero e Agricultura Sustentável; 12. Consumo e Produção Responsáveis